Implementation of Court Decisions Regarding the Payment of Mut'ah, Iddah, And Madhiyah - Bintoro, Septian Cahyo; Tahir, Palmawati; Dwisvimiar, Inge (Universitas Muhammadiyah Sumatera Utara, 2025)
The National Law on Marriage and Compilation of Islamic Law (KHI) has made significant improvements to the implementation of Religious Court judgments on Mut'ah, Iddah, and Madhiyah . This study analyzes legal certainty on the implementation of the Religious Court's decision on these three issues in the Serang and Magelang religious court decisions 0076/Pdt.G/2017/PA.Mgl and legal settlements between the parties regarding maintenance. The research technique is empirical normative legal research on laws and regulations connected to the Serang religious court decision 1570/Pdt.G/2020/PA.Srg and the Magelang religious court decision 0076/Pdt.G/2017/PA.Mgl. Secondary data from court decisions and interviews, scientific journals, and internet media are used in the research data source. The analysis shows that decisions 1570/Pdt.G/2020/PA.Srg and 0076/Pdt.G/2017/PA.Mgl fulfilled the legal certainty requirement of Law Number 16 of 2019 on legal obligations. of Mut' ah, iddah, and madhiyah. However, in completing the implementation of the decision number 1570/Pdt.G/2020/PA.Srg it has not been carried out in its entirety in relation to the payment of living expenses that must be made by the respondent. Alternatives to this are mediation, negotiation, or going through court